MODELING OF A VIBRATORY CLEANING DEVICE WITH COSINOSOIDAL AND SINUSOIDAL SHAPES IN MATCHING THE LONGITUDINAL AND TRANSVERSE CUTTING SURFACE - Mamaxonov, A’zam; Khikmatillaev, Ismoilkhon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article analyzes scientific research conducted on vibratory cleaning devices. Based on the analysis, a new vibratory cleaning machine with longitudinal and transverse cross-sections of cosinusoidal and sinusoidal shape, respectively, is proposed. The motion law of cottonseeds on the screen surface was determined. Graphs were obtained showing the relationship between the longitudinal vibration amplitude and period of the screen surface and the cleaning efficiency.